Agreement Analysis between Sonographic Estimates and Birth Weight, by the WHO and Intergrowth-21st Tables, in Newborns of Diabetic Mothers - Souza, Marcus Vinícius Rodrigues de; Fróes, Lívia Pinto e; Cortez, Pedro Afonso; Lauria, Márcio Weissheimer; Aguiar, Regina Amélia Lopes de; Rajão, Kamilla Maria Araújo Brandão (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2021)
Objective To analyze the agreement, in relation to the 90th percentile, of ultrasound measurements of abdominal circumference (AC) and estimated fetal weight (EFW), between the World Health Organization (WHO) and the International Fetal and Newborn Growth Consortium for the 21st Century (intergrowth-21st) tables, as well as regarding birth weight in fetuses/newborns of diabetic mothers.Methods Retrospective study with data from medical records of 171 diabetic pregnant women, single pregnancies, followed between January 2017 and June 2018. Abdominal circumference and EFW data at admission (from 22 weeks) and predelivery (up to 3 weeks) were analyzed. These measures were classified in relation to the 90th percentile. The Kappa coefficient was used to analyze the agreement of these ultrasound variables between the WHO and intergrowth-21st tables, as well as, by reference table, these measurements and birth weight.Results The WHO study reported 21.6% large-for-gestational-age (LGA) newborns while the intergrowth-21st reported 32.2%. Both tables had strong concordances in the assessment of initial AC, final AC, and initial EFW (Kappa = 0.66, 0.72 and 0.63, respectively) and almost perfect concordance in relation to final EFW (Kappa = 0.91). Regarding birth weight, the best concordances were found for initial AC (WHO: Kappa = 0.35; intergrowth-21st: Kappa = 0.42) and with the final EFW (WHO: Kappa = 0.33; intergrowth- 21st: Kappa = 0.35).Conclusion The initial AC and final EFW were the parameters of best agreement regarding birth weight classification. The WHO and intergrowth-21st tables showed high agreement in the classification of ultrasound measurements in relation to the 90th percentile. Studies are needed to confirm whether any of these tables are superior in predicting short- and long-term negative outcomes in the LGA group.
Keywords: abdominal circumference; estimated fetal weight; birth weight; gestational diabetes; growth charts